Subaqueous speleothems (Hells Bells) formed by the interplay of pelagic redoxcline biogeochemistry and specific hydraulic conditions in the El Zapote sinkhole, Yucatán Peninsula, Mexico - Ritter, Simon M.; Isenbeck-Schröter, Margot; Scholz, Christian; Keppler, Frank; Klose, Lukas; Schorndorf, Nils; Stinnesbeck, Wolfgang (Biogeosciences, 2019)
Abstract. Unique bell-shaped underwater speleothems were recently reported from the deep (- 55 m) meromictic El Zapote sinkhole (cenote) on the Yucatán Peninsula, Mexico. The local diving community has termed these speleothems as Hells Bells because of their shape and appearance in a dark environment in - 28-38 m water depth above a sulfidic halocline. It was also suggested that Hells Bells form under water, yet the mystery of their formation remained unresolved. Therefore, we conducted detailed hydrogeochemical and geochemical analyses of the water column and Hells Bells speleothems including stable carbon isotopes. Based on the comprehensive results presented in this study we deduce that both biogeochemical processes in the pelagic redoxcline and a dynamic halocline elevation of El Zapote cenote are essential for Hells Bells formation. Hells Bells most likely form in the redoxcline, a narrow 1-2 m thick water layer immediately above the halocline where a pelagic chemolithoautotrophic microbial community thrives from the upward diffusion of reduced carbon, nitrogen and sulfur species released from organic matter degradation in organic-rich debris. We hypothesize that chemolithoautotrophy, in particular proton-consuming nitrate-driven anaerobic sulfide oxidation, favors calcite precipitation in the redoxcline and hence Hells Bells formation. A dynamic elevation of the halocline as a hydraulic response to droughts, annual tidal variability and recharge events is further discussed, which might explain the shape of Hells Bells as well as their occurrence over a range of 10 m water depth. Finally, we infer that highly stagnant conditions, i.e., a thick halocline, a low-light environment and sufficient input of organic material into a deep meromictic cenote are apparent prerequisites for Hells Bells formation. This might explain their exclusivity to only a few cenotes in a restricted area of the northeastern Yucatán Peninsula.